THE ROLE OF LAW IN REGULATING HOSPITAL LIABILITY IN THE PANDEMIC ERA - Ayu Miya Maryani; Gunawan Widjaja (Jurnal Kesehatan, 2025)
The role of law in regulating hospital responsibilities in the pandemic era is a very critical aspect to ensure the quality of health services, protection of patient rights, and safety of medical personnel. The law serves as a foundation in setting service standards and protocols that hospitals must adhere to in order to face the challenges posed by the pandemic. In addition, existing laws also protect the rights of patients, including the right to medical information, proper care, and safety while receiving treatment. On the other hand, legal protection for medical personnel is essential to ensure their health and safety at work. With clear and firm regulations in place, all parties involved in the health system-from hospitals, patients, to medical personnel-can work together optimally, creating a safe and effective health system in the midst of a pandemic.